1995
DOI: 10.1073/pnas.92.12.5620
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for five divergent thioredoxin h sequences in Arabidopsis thaliana.

Abstract: Five different clones encoding thioredoxin homologues were isolated from Arabidopsis thaliana cDNA libraries. On the basis of the sequences they encode divergent proteins, but all belong to the cytoplasmic thioredoxins h previously described in higher plants. The five proteins obtained by overexpressing the coding sequences in Escherichia coli present typical thioredoxin activities (NADP+-malate dehydrogenase activation and reduction by Arabidopsis thioredoxin reductase) despite the presence of a variant activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
1
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 43 publications
1
94
1
1
Order By: Relevance
“…With Trx s1r, the reductase exhibits an apparent K m of 13.8 6 2.1 mM with a k cat of 0.27 6 0.02 s 21 . The K m value obtained is similar to that calculated for Trx h2r (13.0 6 1.1 mM) and is in the range of those determined for NTR and Trxs h and m from Arabidopsis and Chlamydomonas reinhardtii (Rivera-Madrid et al, 1995;Stein et al, 1995). However, the k cat value determined for Trx s1r is 5-fold lower than that measured for Trx h2r (1.47 6 0.05 s 21 ), indicating that MtNTRA reduces Trx s1r less efficiently than Trx h2r.…”
Section: Typessupporting
confidence: 66%
“…With Trx s1r, the reductase exhibits an apparent K m of 13.8 6 2.1 mM with a k cat of 0.27 6 0.02 s 21 . The K m value obtained is similar to that calculated for Trx h2r (13.0 6 1.1 mM) and is in the range of those determined for NTR and Trxs h and m from Arabidopsis and Chlamydomonas reinhardtii (Rivera-Madrid et al, 1995;Stein et al, 1995). However, the k cat value determined for Trx s1r is 5-fold lower than that measured for Trx h2r (1.47 6 0.05 s 21 ), indicating that MtNTRA reduces Trx s1r less efficiently than Trx h2r.…”
Section: Typessupporting
confidence: 66%
“…This protein shows only c. 35 % homology to all thioredoxin types known so far (mammalian, m, h or/) which probably explains why its gene has not been detected yet in other animal cells where only two genes have so far been identified, one of which is non-productive (Tonissen & Wells, 1991;Kaghad et al, 1994). Interestingly, in plants at least one and possibly several thioredoxin h show extended N-terminus sequences (Rivera-Madrid et al, 1995), but it is not known whether this represents a signal peptide and whether these proteins are really imported into the mitochondria. Also it is not known whether mitochondria contain a thioredoxin reduction system (namely NADPH -I-thioredoxin reductase).…”
Section: Photosynthetic Organisms (A) Chloroplastic Systemsmentioning
confidence: 99%
“…Thioredoxins h are far more variable with a surprisingly' high number of sequences in a single organism: five complete sequences in the case of A. thaliana (Rivera-Madrid et al, 1995), and three additional expressed sequence tags (EST) (not shown). As evidenced by the tree, the divergence within the A. thaliana thioredoxin h sequences is old, probably preceding the divergence between monocots and dicots.…”
Section: Sequences and Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…An active-site motif of WCGPC is conserved among the classic TRXs of E. coli and many other species. However, other active-site sequences exist, including a WCPPC motif that has been identified in TRX and TRX-like sequences within diverse organisms such as Arabidopsis, Caenorhabditis elegans, and Mus musculus (Rivera-Madrid et al, 1995;Kurooka et al, 1997). The classic TRX has its active site protruding from a highly organized, globular structure composed of five strands of ␤-sheets enclosed by four ␣-helices (Holmgren, 1985).…”
mentioning
confidence: 99%